Sustainable tourism and sustainable development goals (SDGs): a state‑of‑the‑art review of past, present, and future trends - Muhammad Ashraf, Fauzi (Springer, 2023)
This study aims to review the role of sustainable tourism with the sustainable development goals (SDGs). The introduction of SDGs in 2015 has made sustainable tourism much more manageable within a structured and systematic set of goals. A bibliometric approach was applied based on 479 journal publications from the Web of Science database. The study explores the knowledge structure based on past influential publications (document citation analysis), current knowledge structure (co-citation analysis), and future trends (co-occurrence of keywords analysis) on SDGs implementation in the tourism and hospitality industry. Findings suggested that there are several significant clusters based on the three analyses. Theoretical and managerial implications were discussed.